THE IMPACT OF THE NEW STUDENT ADMISSION POLICY (PPDB) WITH THE ZONING SYSTEM ON PRIVATE SCHOOLS IN MALANG CITY: A MULTICASE STUDY - Alfajri, Taufik Akbar; Andarwulan, Trisna (Faculty of Administrative Science, Universitas Brawijaya, 2026)
The New Student Admission Policy (PPDB) with the zoning system aims to create equitable access to education; however, this policy also has significant impacts, particularly on private schools. This study aims to analyze the impact of the PPDB zoning system policy on three private junior high schools in Malang City: SMP Taman Siswa, SMP Muhammadiyah 01, and SMP Sunan Giri. A qualitative descriptive approach was used to provide an in-depth depiction of the phenomenon through interviews, observations, and document analysis. The findings reveal that this policy affects four dimensions: individual, organizational, community, and institutional. The impact on individuals includes a decline in student motivation and economic challenges for teachers. From an organizational perspective, the policy results in a decrease in student enrollment and school income, although it creates opportunities to improve the quality of educational services. In the community dimension, the policy increases parents' economic burden and changes perspectives on the importance of educational quality. Meanwhile, in the institutional aspect, the role of school committees has become more active in fundraising and promotion. This study concludes that while the zoning policy has good intentions, its implementation requires further support from the government to mitigate the negative impacts on private schools. Adaptive strategies from private schools and enhanced synergy between the government, schools, and communities are proposed to create a more inclusive educational ecosystem.